(untitled) (CIPEEX, 2024)
THE ABILITY TO TRANSPOSE TECHNICAL KNOWLEDGE IN THE AREA OF CLINICAL MEDICINE SKILLS INTO EXTENSION ACTIVITIES BY THE HIGHER EDUCATION INSTITUTION IS THE SUBJECT OF THIS STUDY AND DEMONSTRATES THE SUCCESSFUL PARTICIPATION OF MEDICAL STUDENTS FROM A PRIVATE UNIVERSITY IN THE STATE OF GOIS IN UNIVERSITY EXTENSION PROJECTS. OBJECTIVE: TO REPORT ON THE EXPERIENCE OF PREPARING AND RUNNING TWO HEALTH EDUCATION WORKSHOPS GIVEN BY MEDICAL STUDENTS THROUGH THE CURRICULARIZATION OF EXTENSION ACTIVITIES. METHOD: MEETING OF CLASS LEADERS AND EXTENSION MONITORS TO PREPARE INTERACTIVE WORKSHOPS, USING THE PBL TEACHING METHOD, ON THE SUBJECT OF LIFESTYLE HABITS AS PART OF THE ANAMNESIS TECHNIQUE. THE FIRST WORKSHOP FOCUSED ON WATER QUALITY AND ITS DIRECT RELATIONSHIP WITH THE TRANSMISSION OF DISEASES, ESPECIALLY THOSE LINKED TO THE GASTROINTESTINAL SYSTEM. THE PUBLIC SCHOOL STUDENTS LEARNED ABOUT THE IMPORTANCE OF ENSURING THAT WATER MEETS CHEMICAL AND MICROBIOLOGICAL QUALITY STANDARDS, AVOIDING DISEASES SUCH AS CHOLERA AND DIARRHEA. THE SECOND WORKSHOP DEALT WITH ADOLESCENTS’ LIFESTYLE HABITS, INCLUDING DIET, PHYSICAL ACTIVITY, SLEEP AND OTHER ASPECTS RELATED TO WELL-BEING. THE STUDENTS WERE ENCOURAGED TO CARRY OUT A SELF-ASSESSMENT OF THEIR OWN HABITS USING A QUESTIONNAIRE CALLED "THE WHEEL OF LIFE", REFLECTING ON HOW THEIR CHOICES AFFECT THEIR HEALTH. BOTH WORKSHOPS PROMOTED A HOLISTIC UNDERSTANDING OF THE IMPORTANCE OF WATER AND HEALTHY LIFESTYLE HABITS IN PROMOTING HEALTH, THROUGH INTERACTIVE QUESTIONNAIRES ON MULTIMEDIA RESOURCES AVAILABLE AT THE EDUCATIONAL UNIT WHERE THE ACTIVITY TOOK PLACE. RESULTS: THE STUDENTS WERE EMPOWERED TO MAKE CONSCIOUS CHOICES TO IMPROVE THEIR QUALITY OF LIFE. THE QUESTIONNAIRE INSTRUMENT WAS USED AS A TOOL FOR STUDENTS’ SELF-AWARENESS, ALLOWING THEM TO ASSESS THEIR CURRENT STATE AND UNDERSTAND HOW THEIR HABITS INFLUENCE THEIR QUALITY OF LIFE. THESE WORKSHOPS PROVIDED A VALUABLE OPPORTUNITY FOR MEDICAL STUDENTS TO SHARE KNOWLEDGE WITH THE STUDENT COMMUNITY, PROMOTING AN EXCHANGE OF INFORMATION AND EXPERIENCES. THE USE OF MULTIMEDIA RESOURCES, PRACTICAL ACTIVITIES AND INTERACTIVE DIALOG MADE IT EASIER FOR HIGH SCHOOL STUDENTS TO UNDERSTAND THE CONTENT. CONCLUSION: THE INTERCONNECTION BETWEEN WATER QUALITY AND HEALTHY LIFESTYLE HABITS WAS HIGHLIGHTED, HIGHLIGHTING HOW DAILY CHOICES, INCLUDING THE QUALITY OF WATER CONSUMED, CAN DIRECTLY IMPACT STUDENTS’ HEALTH AND WELL-BEING. SUCH ACTIVITIES REPRESENT AN EFFECTIVE MODEL OF HEALTH EDUCATION, EMPOWERING ADOLESCENTS TO MAKE INFORMED DECISIONS ABOUT THEIR HEALTH AND LIFESTYLE. IN ADDITION, THE DATA COLLECTED OFFERS OPPORTUNITIES FOR FUTURE RESEARCH THAT CAN DEEPEN UNDERSTANDING OF THESE ISSUES AND MEASURE THE IMPACT OF THE WORKSHOPS ON THE HEALTH OF THE PARTICIPANTS AND THE WIDER COMMUNITY. THE "SOWING HEALTH" PROJECT DEMONSTRATES THE IMPORTANCE OF A HOLISTIC APPROACH TO PROMOTING HEALTHY LIVING AND HIGHLIGHTS THE COMMITMENT OF FUTURE HEALTH PROFESSIONALS TO PROMOTING PUBLIC HEALTH.